Cambrian Hyolitha of Siberian, Baltican and Avalonian aspect in east Laurentian North America: taxonomy and palaeobiogeography. Issue 2 (3rd April 2019) - Malinky, John M.; Geyer, Gerd
Abstract : Malinky, J.M. & Geyer, G., 6 March 2019. Cambrian Hyolitha of Siberian, Baltican and Avalonian aspect in east Laurentian North America: taxonomy and palaeobiogeography. Alcheringa 43, 171–203. ISSN 0311-5518. Newly identified hyoliths from early Cambrian 'Small Shelly Fossil' assemblages in New York State and Quebec extend the geographical ranges of hyolith taxa, otherwise known only from Baltica and Siberia, into eastern Laurentian North America, and in some cases, are accompanied by significant stratigraphical range extensions. The newly recognized taxa from this region include the hyolithids Hexitheca washingtonensis sp. nov., Aimitus sp., A . sp. cf. A. communis, Anabaricornus sp., Similotheca americana, Grantitheca glenisteri, and the orthothecids Decoritheca sp., Contitheca sp., two species of Holmitheca, and two hyolith species that can not be confidently assigned to an order at this time. Early Cambrian limestone clasts within the Lower Ordovician of Quebec have produced the hyolithids Similotheca americana and Nevadotheca princeps . The occurrences of Aimitus, Anabaricornus, and Holmitheca provide a palaeobiogeographical link with hyolith assemblages in Siberia, and Hexitheca to Baltica. Contitheca not only is known from these areas, but also has been found in west Laurentia, Morocco, Korea and Antarctica. A review of previously named species demonstrates that none of their type materials can be confidently referred to genus or species level because of poor preservation. John M. Malinky [ jmalinky@sbcglobal.net ], Department of Physical Science, San Diego City College, 1313 Park Boulevard, San Diego, CA 92101, USA; Gerd Geyer* [ gerd.geyer@uni-wuerzburg.de ], Institut für Geographie und Geologie, Bayerische Julius-Maximilians-Universität Würzburg, Am Hubland, 97074 Würzburg, Germany.